Criterios de superficie verde por habitante en ciudades pequeñas basados en modelos de densidad y proximidad urbana. Caso: Cabecera parroquial de Patate.” - Solano Freire, Joselyn Elizabeth (2025)
The main objective of this thesis is to implement green space per capita criteria in small cities by applying density and urban proximity models, with a specific focus on the urban center of Patate, Ecuador. This approach aims to address the equitable distribution of green areas, optimizing their accessibility and functionality to enhance the quality of life for residents and foster sustainable urban development. The research methodology is based on a positivist paradigm with a quantitative approach, involving data collection and analysis to test a hypothesis. International models of urban density and proximity were integrated to develop green space criteria tailored to the specific characteristics of small cities like Patate. The project follows a cross-sectional study design with non-probabilistic intentional sampling. Deductive and inductive methods were combined to assess the problem and propose viable solutions. The diagnosis of Patate's current situation, based on 13 indicators of urban sustainability and quality of life, reveals significant challenges and opportunities. Adequate density levels were observed in some areas, along with a compact structure around the central park that reduces travel distances. However, low levels of green space per capita and proximity to green areas were identified, along with deficiencies in pedestrian infrastructure and inefficient land use due to vacant lots and low compactness. Threats such as uncontrolled urban growth, functional segregation, and limited investment in public spaces were also noted. The application of density and urban proximity models allowed for the evaluation of the correlation between these factors and green space through linear regression analysis. The results showed a positive correlation, indicating that integrating these criteria into green area planning can significantly improve urban quality of life in small cities like Patate.